2015
DOI: 10.1039/c5ce01432h
|View full text |Cite
|
Sign up to set email alerts
|

The influence of reaction media on CdIn2S4 and ZnIn2S4 nanocrystallite formation and growth of mesocrystal structures

Abstract: Hot-injection method for synthesis of CdIn2S4 in three different compositions of organic media/solvents was studied. Nanosized CdIn2S4 is successfully synthesized in oleic acid/oleylamine mixture of complexing/capping agents. Obtained mesocrystals of 20-30 nm in diameter are self-organized in marigold-like structures. Estimated band-gap of synthesized semiconductor is far in visible spectral region and has a value of 2.1eV. Potential of band edges is calculated using empirical equation. As-prepared material wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The peak in the XRD diffractograms around 25°, unexpected for zinc blende crystals, has been found more often in the literature for a variety of zinc blende materials 25,42−44 and can be assigned to metal−ligand complexes on the surface of the QDs. 43,44 We remark that the InZnP QD cores showed a lattice parameter similar to bulk InP, suggesting only little Zn was incorporated. ICP-OES and XPS revealed that the In:Zn ratio (6:1) was indeed much lower than the feed fraction (2:1).…”
Section: ■ Results and Discussionmentioning
confidence: 84%
“…The peak in the XRD diffractograms around 25°, unexpected for zinc blende crystals, has been found more often in the literature for a variety of zinc blende materials 25,42−44 and can be assigned to metal−ligand complexes on the surface of the QDs. 43,44 We remark that the InZnP QD cores showed a lattice parameter similar to bulk InP, suggesting only little Zn was incorporated. ICP-OES and XPS revealed that the In:Zn ratio (6:1) was indeed much lower than the feed fraction (2:1).…”
Section: ■ Results and Discussionmentioning
confidence: 84%
“… , Moreover, the diffraction peak marked by ▼ corresponds to the crystal face (220) of cubic CdIn 2 S 4 (JCPD standard card no. 27-0060) . In addition, the diffraction peaks of CuS cannot be observed from XRD patterns.…”
Section: Resultsmentioning
confidence: 99%
“…27-0060). 42 In addition, the diffraction peaks of CuS cannot be observed from XRD patterns. This result is attributed to the low amount of Cu doping which cannot be detected.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In addition to the four main synthetic methods mentioned earlier, many other methods for synthesizing ZIS photocatalysts have also been reported, such as a hot-injection method, [56,57,110] chemical vapor deposition, [111] spray pyrolysis, [112][113][114][115] and so on. For instance, Carevic et al prepared ZIS nanosheets and nanotubes with the bandgaps in the range from 2.6 to 3.0 eV through the hot-injection method in oleicacid/oleylamine media.…”
Section: Other Synthetic Methodsmentioning
confidence: 99%
“…[ 55 ] Carevic et al first reported a preliminary experiment on the synthesis of ZIS using the oleic acid/oleylamine combination. [ 56 ] They got a mixed binary/ternary sulfide, where the ZIS grows in the form of flakes and over time start to roll, forming tubes. The results showed the beginning of tube formation.…”
Section: Fundamental Properties Of Zis As Photocatalystmentioning
confidence: 99%